Os impactos do uso de tecnologia da informação e da identificação e captura automática de dados nos processos operacionais do varejo - Romano, Regiane Relva (2011)
This study sought to identify the main IT technologies available for the AIDC and retail self-service area, to fill the gap in the literature about the real advantages of using new technologies at the point of sale, in order to optimize its operation. In order to do this, we studied the main operational processes of a self-service retail store bearing in mind to identify how the technologies of Automatic Identification and Data Capture and IT could help to improve the operating results and add value to the business. To analyze these proposals we have surveyed several global case studies of retail companies, which implemented the AIDC and IT technologies to investigate what were the impacts of using these technologies in their operations and then designed a comprehensive and innovative Case Study, through which we sought to understand the real business benefits. As a final result, it was possible to identify the changes and the benefits in terms of cost, productivity, quality, flexibility and innovation. The work also highlighted the critical points of success for the implementation of AIDC and IT Retail, which are: the review of operating processes, the correct definition of the hardware; inputs; software; interferences of the physical environment, the availability of data / information of products, of people / employees and of business partners / suppliers. More specifically, this study sought to contribute to the enrichment of the field studies in the retail segment and for the use of information technology in Brazil, since the issue on the use and impact of new technologies at the point of sales, still remains unexplored academically.